Body image and quality of life in women with breast cancer: Appreciating the body and its functionality. (March 2022) - Ettridge, Kerry; Scharling-Gamba, Katrine; Miller, Caroline; Roder, David; Prichard, Ivanka
Highlights: Body image assessment in breast cancer commonly focuses on body dissatisfaction. We explored body and functionality appreciation, body dissatisfaction and QoL. Results indicate relevance of positive and negative body image in QoL. Breast cancer-specific measures of positive body image may increase understanding. Research on interventions targeting positive and negative body image is desirable. Abstract: Women with breast cancer often experience major physical changes, which can impact their body image and Quality of Life (QoL). Traditional assessments of body image implemented within breast cancer research focus solely on body dissatisfaction. This study explored the association between both positive and negative body image and QoL. Australian women ( N = 123) within 5-years of a breast cancer diagnosis were invited to complete a web-based questionnaire including measures of body appreciation and functionality appreciation, cancer-specific measures of body dissatisfaction and QoL, and demographic, health and treatment/illness questions. All body image measures were significantly associated with QoL ( p < .01). However, when body image variables were entered simultaneously as predictors of QoL (adjusting for comorbidity, treatment and employment), only body dissatisfaction was significantly associated with QoL ( p < .001). Further analyses indicated this was due to shared variance in QoL between body and functionality appreciation, suggesting they assess highly related constructs within this population. Results indicate positive and negative components of body image are relevant to QoL within breast cancer populations; though, body dissatisfaction remained the strongest predictor of QoL indicating its pervasiveness. Future research should explore the development and use of breast cancer-specific measures of positive body image.